Planning and evaluating undergraduate dissertations: an experience at the Carlos III University Bachelor’s Degree in Information and Documentation - Ortiz-Repiso, Virginia; García Zorita, Carlos; Pacios, Ana R.; Vianello, Marina (Revista General de Información y Documentación, 2014)
In the framework of the European Higher Education Area, the Undergraduate Dissertation is a subject on the official curriculum for the bachelor’s degrees that can be earned in Spanish universities, Carlos III University of Madrid among them. It consists of an individual dissertation in which students apply the knowledge, skills and competencies acquired throughout their 4-year courses to a problem specific to the discipline associated with the degree to which they aspire. Planning, conducting and evaluating the work involved in the dissertation call for ad hoc tools that must be designed to accurately appraise the command of specific competencies associated with the degree sought by the student. The present paper introduces three such tools developed for the Bachelor’s Degree in Information and Documentation offered at Carlos III University since 2008-09: a guidance manual, a preview system and an evaluation rubric. The guidance manual provides students with clear and precise instructions on how to undertake their study. The preview system affords a consistent, clear procedure for all students and for suitable monitoring of their progress at specified intervals. The evaluation rubric is a consistent and objective marking tool for juries. The three enable students and staff to suitably monitor progress and for professors to consistently and objectively evaluate all students in accordance with the duly weighted categories into which the competencies associated with the bachelor’s degree in Information and Documentation are grouped.